Attitudes of Heterosexual Men and Women Toward HIV Negative and Positive Gay Men - Pala, Andrea Norcini (J Homosex, 2016)
Attitudes of Italian heterosexual men and women toward gay men, both HIV positive and negative, are poorly investigated. Italian culture is still extremely conservative and provides limited support to the gay community (e.g., lack of same-sex marriage recognition). Consequently, gay men experience social exclusion and disparities. The present study explores the association between homophobia and closeness with sexual orientation and HIV status. 261 heterosexual Italian men and women were assessed for feelings of closeness and homophobia after reading a vignette where the character was C1: heterosexual and HIV negative; C2: gay and HIV negative; or C3: gay and HIV positive. Experiences of homophobia and closeness varied depending on gender of participant and condition assigned, and higher levels of homophobia were correlated with lower levels of closeness regardless of HIV status. Implications and future directions are discussed.